PERAN PERLINDUNGAN INDIKASI GEOGRAFIS MENUJU KESEJAHTERAAN NASIONAL MENURUT TEORI FRIEDMAN - Pramudhyna Ayuningtyas; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
This scientific work aims to explore and describe the role of protecting geographical indications as one of the substructures for the enlargement of the creative economy towards a prosperous country. The writing method used in this scientific work is normative juridical (normative legal research method) with the Statute Approach and Conceptual Approach. The results of this scientific work are expected to show that creative economic growth based on Geographical Indications in Indonesia is quite rapid and can be utilized and developed as a means towards a prosperous Indonesia.Keywords: Creative Economy; Geographical Indications; Welfarestate